Application of flipped classroom combined with case-based learning in Introduction to Environmental Health Science - You Li; You Li; Liang Cao; Liang Cao; Huixia Zhang; Huixia Zhang; Weiyi Pang; Weiyi Pang; Yan Sun; Yan Sun; Zhiyong Zhang; Zhiyong Zhang (Frontiers Media S.A., 2023)
ObjectivesTo explore the effect of flipped classroom combined with case-based learning in Introduction to Environmental Health Science for the Master of Public Health (MPH).MethodsThe MPH Master's class of 2022 was selected as the experimental group at Guilin Medical University from September to December 2022, and the flipped classroom combined with the case-based learning was adopted. The class of 2021 was the control group, and we taught them with the traditional teaching method. A self-designed questionnaire and academic performance were used to evaluate the teaching effects of the two groups.ResultsThere was no difference in the paper score between grades 2022 and 2021, and the design question score of grade 2022 was higher than that of grade 2021. The difference was statistically significant (p < 0.05). The students in grade 2022 had a high overall recognition of the teaching effect of the flipped classroom combined with case-based learning in Introduction to Environmental Health Science.ConclusionThe teaching method of the flipped classroom combined with case-based learning is more suitable than the traditional teaching method in the Introduction to Environmental Health Science for MPH. It can stimulate the independent learning ability of MPH students and improve their ability to use knowledge and an innovative spirit.